Dakwah dalam Perspektif Modernisme Antisipasi menuju Postmodernisme - Syam, Nia Kurniati (Mediator, 2005)
Dakwah in the age of postmodernism has faced serious challenge due to the high tempo of information exchange which transform communication and cultural landscape of society. Postmodernism essentially rejected the universality of science and ideology. Postmodernism also challenge the neutrality of technology. Postmodernism challenge toward dakwah is aimed to the concept of dakwah itself. Is it possible to communicate Islamic messages in postmodernism era? The author offers five principles for dakwah strategies consisted of synergy, accumulation, convergence, totality, and inclusiveness.